Anticholinergic Syndrome Following Datura metel Ingestion in an Adolescent: A Case Report - Lucia Pudyastuti Retnaningtyas; Nur Flora Nita Taruli Basa Sinaga; Lili Soetjipto (Publication Department, Universitas Warmadewa, 2026)
Background: Datura metel, locally known as kecubung, contains tropane alkaloids that may induce anticholinergic toxicity. Adolescents may intentionally ingest the plant due to curiosity about its psychoactive effects. Case presentation: A 13-year-old boy presented with agitation, delirium, palpitations, and incoherent speech three hours after ingesting approximately one glass of a decoction made from Datura metel flowers. Examination revealed altered mental status (Glasgow Coma Scale E3V4M6), bilateral mydriasis with sluggish light reflex, and dry mucous membranes. Vital signs were stable. Laboratory investigations, including blood glucose and serum electrolytes, were within normal limits. Electrocardiography showed sinus arrhythmia. The patient received supportive management including oxygen therapy, intravenous fluids, activated charcoal, and oral neostigmine. He was admitted to the Pediatric Intensive Care Unit and showed clinical improvement within eight hours, with complete recovery after three days. At one-week follow-up, the patient remained asymptomatic. Conclusion: Early recognition of anticholinergic toxidrome based on clinical features and exposure history is essential. Supportive management can result in favorable outcomes even when specific antidotes are unavailable.